(untitled) (JS (JURNAL SEKOLAH), 2019)
Abstract: Improving Students’ Mathematical Concept Understanding Through the Application of Cooperative Learning Models for Class XII Discovery Learning 2. The application of cooperative learning strategies Discovery Learning will be one of the effective learning strategies, and the Cooperative Learning Learning model using the help of Worksheets (LKPD), will provide a major contribution in improving the understanding of the concept of mathematics in class XII IPA2 SMA Negeri 9 Pekanbaru. From the results of observations in the first and second cycles, it was shown in the increase in the final results of each cycle, namely in the first cycle the average value of students reached 69.08 with a classical completeness of 68.42%, in the second cycle an increase in the average value of students reached 82 , 89 with classical completeness 84.21%. Keywords: Mathematics, learning models, cooperative discovery learning Abstrak: Meningkatkan Pemahaman Konsep Matematika Siswa Melalui Penerapan Model Pembelajaran Kooperatif Discovery Learning Kelas XII IPA 2. Penerapan strategi pembelajaran Kooperatif Discovery Learning akan menjadi salah satu strategi pembelajaran yang efektif, dan model pembelajaran Kooperatif Discovery Learning menggunakan bantuan Lembar Kerja (LKPD), akan memberi kontribusi yang besar dalam peningkatan pemahaman konsep mata pelajaran matematika pada kelas XII IPA2 SMA Negeri 9 Pekanbaru. Dari hasil observasi pada siklus I dan II, ditunjukan pada peningkatan hasil akhir tiap siklus yaitu pada siklus I nilai rata“rata peserta didik mencapai 69,08 dengan ketuntasan klasikal 68,42%, pada siklus II terjadi peningkatan nilai rata “ rata siswa mencapai 82,89 dengan ketuntasan klasikal 84,21%. Kata Kunci: Matematika, model pembelajaran, kooperatif discovery learning